The Maintenance of Marsela West Language in Nura Village - Wakim, Yohana Lolita; Rumalean, Iwan; da Costa, Romilda Arivina (Universitas Pattimura, 2023)
This study examines the preservation of the West Marsela language in Nura Village, Masela District, Southwest Maluku Regency. This study is a post-positivist descriptive qualitative research. The study was carried out at Nura Village, Masela District, Southwest Maluku Regency. The physical boundaries are as follows: to the west, Babar Island; to the east, the Tanimbar Islands; to the north, Dawelor Island; and to the south, the Australian Sea. The research was carried out from January 23, 2023, until February 23, 2023. This study's data includes verbal expressions in the vocabulary of the West Marsela language, utilized by the inhabitants of Nura Village, Masela District, West Southeast Maluku Regency. The data collection techniques employed included field notes, interviews, and documentation. The researcher serves as the instrument in this study, supported by a job analysis table. The findings of this study suggest that the preservation of the West Marsela language is confined to familial and religious contexts, with minimal utilization among children and adolescents. The percentage data reveals that in the family domain, the maintenance of the West Marsela language is 10% for children, 10% for adolescents, 40% for adults, and 100% for the elderly. In the religious domain, usage is 0% for children, 33% for adolescents, 67% for adults, and 67% for the elderly. The utilization of the West Marsela language among children and adolescents is significantly constrained, as they predominantly employ Ambon Malay.